The Coverage of Xenophobia Research Findings by the Mail & Guardian and the Sowetan, 2008-2013. - Vanyoro, Kudakwashe P. (Midlands State University, 2017)
One of the media’s core and normative roles is to inform, educate and entertain society. This dissertation unravels this notion. It investigates the coverage of xenophobia research findings in two popular South African newspapers; the Mail & Guardian and the Sowetan from 2008 to 2013. Employing a neo-Foucauldian approach informed by Michel Foucault’s theory of discourse, power and knowledge, and using mixed methods, this study calls for more balanced and consistent coverage of xenophobia research findings by the South African press. Second, it calls for greater awareness by journalists of the potential role of research findings in contributing positively to migrant inclusion, and in creating a better understanding of the many dynamics sorrounding xenophobia. It does this by identifying and discussing three key findings. First, that the coverage of xenophobia findings in the two newspapers between 2008 and 2013 was largely a case of classical reactive reporting. The two newspapers reported more on xenophobia and findings only when xenophobia turned violent, as was the case in 2008. Second, that the two newspapers reported ‘using’ findings more than they actually reported ‘on’ findings. This suggests that journalists used research in order to qualify their viewpoints, rather than reporting objectively. Third, that there was clear tension between the discourses of ‘empirical knowledge’ and ‘popular perceptions’; evident in a majority of texts I analysed. This exposed the polarisation between popular discourses about migration, which are largely negative, and research, which largley shows that migration contributes positively to the South African economy. This study concludes by providing recommendations for best practice to journalists and researchers working on xenophobia reporting and research respectively in South Africa, setting an important agenda for more research on the ‘re-presentation of a representation’ by the media, more especially when dealing with contentious topics like migration.